Last glacial geomorphologic records in Mt Chelmos, North Peloponnesus, Greece - Pavlopoulos, Kosmas (2018)
This study deals with the analysis of the glacial processes that have affected the relief of Mt Chelmos in northern Peloponnesus, Greece during middle and Late Pleistocene. The goal was to compile a combined geomorphological-geological map of the study area which would enable the chronological stratification of the glacial landforms cropping up on Mt. Chelmos. Chronological stratification was further aided by optically stimulated luminescence (OSL) dating. The map served as the basis upon which the reconstruction and discussion on the phases of the Middle-Late Quaternary paleoclimatic history of Mt. Chelmos have been made. A sophisticated semiautomated method was first used to analyze the Digital Elevation Model (DEM), combined with Aster, Quickbird and ALOS imagery in order to identify glacial and periglacial, as well as karstic features. Then, these features along with other nonrecognizable features from the remote-sensing images were documented in the field. In this way, several glacial landforms were identified, such as moraines and cirques, indicating extended glaciation phases during the middle and Late Pleistocene. Additionally, a ground moraine located at an altitude of 1900-2050 m, within the Spanolakos glacial valley, was dated using the OSL-dating method. The resulting ages indicate a phase of glacier advance/stabilization during MIS-5b (89-86 ka), which is in consistence with pollenrecord evidence from Greece and the Mediterranean. © 2018, Science Press, Institute of Mountain Hazards and Environment, CAS and Springer-Verlag GmbH Germany, part of Springer Nature.